2010
DOI: 10.2486/indhealth.ms1041
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Adsorption Capacity of Coconut Shell Activated Carbon for Organic Vapors Due to Moisture Contents

Abstract: In occupational hygiene, activated carbon produced from coconut shell is a common adsorbent material for harmful substances including organic vapors due to its outstanding adsorption capacity and cost advantage. However, moisture adsorption of the carbon generally decreases the adsorption capacity for organic vapors. In a previous report, we prepared several coconut shell activated carbons which had been preconditioned by equilibration with moisture at different relative humidities and measured the breakthroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…We found that the relative percent weight increase due to moisture adsorption of the carbon specimen had a quantitative effect 2,3) on reducing the breakthrough time. That is, the data plots of the breakthrough times versus water adsorption showed good agreement with quadratic functions approximating a wide range of water adsorption in the graphs 2,3) .…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…We found that the relative percent weight increase due to moisture adsorption of the carbon specimen had a quantitative effect 2,3) on reducing the breakthrough time. That is, the data plots of the breakthrough times versus water adsorption showed good agreement with quadratic functions approximating a wide range of water adsorption in the graphs 2,3) .…”
Section: Introductionmentioning
confidence: 56%
“…Activated carbon plays an important role in occupational and industrial hygiene as an adsorbent of harmful substances, particularly various types of organic vapor. In the actual use of an activated carbon bed in respirator gas filters, the breakthrough characteristics of organic vapors are very important, and these characteristics are affected by water adsorption of the activated carbon bed and humidity in the test gas [1][2][3] . Previously 2,3) , we prepared several activated carbon beds using coconut shell activated carbon preconditioned by equilibration with moisture at different relative humidities (RH), and measured the breakthrough times for several types of organic vapor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular probes technique is tedious and time-consuming in terms of the experimental procedure [12]. Despite several studies describing adsorption of OV onto activated carbon [3,[18][19][20]22,23] and using only one type of OV and a reference compound to characterize the pore structure, this approach may not be suitable for all compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is the preferred adsorbent material for the removal of toxic organic vapors given its low cost, high specific surface area, extensive pore volume, and tunable pore size distribution depending on the activation process used [1][2][3][4]. Particularly, activated carbon is widely used in the removal of toxic vapors from the ambient air by a process known as physical adsorption [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of papers where the results for micropreconcentrators are given. In [17] and [18] the CF for benzene for different adsorbent materials, various adsorption conditions and benzene mixture with other gases are featured. However, it is difficult to find an information about acetone densification using micropreconcentrator structures.…”
mentioning
confidence: 99%